Solve for v -6/7v=18

Math
-67v=18
Multiply both sides of the equation by -76.
-76⋅(-67)⋅v=-76⋅18
Simplify both sides of the equation.
Tap for more steps…
Simplify -76⋅(-67)⋅v.
Tap for more steps…
Cancel the common factor of 7.
Tap for more steps…
Move the leading negative in -76 into the numerator.
-76⋅(-67)⋅v=-76⋅18
Move the leading negative in -67 into the numerator.
-76⋅-67⋅v=-76⋅18
Factor 7 out of -7.
7(-1)6⋅-67⋅v=-76⋅18
Cancel the common factor.
7⋅-16⋅-67⋅v=-76⋅18
Rewrite the expression.
-16⋅-6⋅v=-76⋅18
-16⋅-6⋅v=-76⋅18
Cancel the common factor of 6.
Tap for more steps…
Factor 6 out of -6.
-16⋅(6(-1))⋅v=-76⋅18
Cancel the common factor.
-16⋅(6⋅-1)⋅v=-76⋅18
Rewrite the expression.
-1⋅-1⋅v=-76⋅18
-1⋅-1⋅v=-76⋅18
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅v=-76⋅18
Multiply v by 1.
v=-76⋅18
v=-76⋅18
v=-76⋅18
Simplify -76⋅18.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Move the leading negative in -76 into the numerator.
v=-76⋅18
Factor 6 out of 18.
v=-76⋅(6(3))
Cancel the common factor.
v=-76⋅(6⋅3)
Rewrite the expression.
v=-7⋅3
v=-7⋅3
Multiply -7 by 3.
v=-21
v=-21
v=-21
Solve for v -6/7v=18

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top